Digital Technologies in Authentic Assessment in Higher Education: A Systematic Literature Review and Narrative Synthesis - Anjin Hu; Qian Liu; Ben Daniel (SAGE Open, 2025)
Authentic assessment is widely recognized as a valuable method that reflects real-world contexts, allowing students to apply their knowledge to practical challenges and prepare for their futures. Despite the pervasive influence of digital technologies in modern work and life, their role in authentic assessment—an approach centered on real-world relevance—remains poorly understood. Key questions persist regarding how digital technologies are integrated into authentic assessment practices. This review examines the nature and extent of technology integration in authentic assessment within higher education literature. Through a systematic search, identification, analysis, and synthesis, we identified 52 relevant studies. Our findings reveal significant variation in technology use across the four steps of authentic assessment. While digital tools are commonly employed in assessment task design (Step 2), there is limited consideration of broader digital contexts (Step 1) or integration into evaluative judgments and feedback mechanisms (Steps 3 and 4). We also identify diverse approaches to incorporating technology within the design phase. These differences in technology use reflect varying conceptualizations of authentic assessment, influencing its design, implementation, and learning outcomes. To provide educators with practical guidance, we build on a widely adopted stepwise model by introducing a structured framework for integrating digital technologies into authentic assessment. Finally, we highlight areas for future research and practice that may enhance authentic assessment through technology.